TEACHERS’ PERSPECTIVES ON JARIMATIKA, KUMON, AND ABACUS METHODS TO IMPROVE STUDENTS’ MATHEMATICS EFFECTIVENESS - Salsabila, Alisa; ardae, rifqi; Wahyunengsih (Relevan : Jurnal Pendidikan Matematika, 2025)
This Study aims to determine teachers’ views on the effectiveness of jarimatika, kumon, and abacus methods in improving junior high school students’ mathematics abilities. This Study uses a qualitative approach with data sources from one mathematics teacher and 27 junior high school students at Nurul Huda Witthaya School. The research instruments are interviews and Google Forms with data collection techniques through literature studies, questionnaires, and interviews. Data analysis techniques use content analysis and thematic categorization. The study results indicate that teachers tend to choose the Kumon method because it is considered systematic and practical at the junior high school level. At the same time, students prefer jarimatika because it is considered easy and fun. The conclusion of this Study shows the need for adjustments to mathematics learning methods that pay attention to the effectiveness of student interest and learning. This Study suggests a balanced integration approach between pedagogical needs and student preferences.